Relationships between anaerobic performance, field tests, and functional level of elite female wheelchair basketball athletes - Molik, B.; Laskin, J. J.; Kosmol, A.; Marszalek, J.; Morgulec-Adamowicz, N.; Frick, T. (Human Movement, 2013)
The aim of this study was to evaluate the associations between anaerobic performance (AnP), applicable field tests, and the functional classification levels in female wheelchair basketball athletes. Methods. Female wheelchair basketball athletes (N = 23; Category A, n = 9; Category B, n = 14) from the Canadian national team were evaluated using field tests and the 30-second Wingate Anaerobic Test. Measures of peak power output (PP), time to achieve peak power (tPP), mean power output (MP), and a fatigue index (FI) were used to assess AnP. A test battery evaluating seven wheelchair basketball skills was applied. Student`s t test was used to identify differences between the two main functional categories (A and B). Spearman`s rank correlation coefficient and Pearson`s product-moment correlation coefficient were calculated to determine the significance of all relationships between the parameters of AnP, the results of the field tests, and the eight functional classification levels of the athletes (1.0-4.5 pts.). Results. In all analyzed parameters, except for the field test measuring shooting skills, the results of AnP were significantly higher for Category B players. Significant relationships were observed between athletes` classification level and AnP and the field tests except for tPP, the 5 m sprint, and the shooting test. The strongest association was observed for MP and PP, MP and FI, PP and FI (p = 0.001). Conclusions. Strong associations were found between the functional classification level and AnP of the female wheelchair basketball athletes. The strongest correlation was confirmed between MP, PP, and the field test measuring the two-handed chest pass, suggesting that this test can be used to indirectly assess the anaerobic performance of female wheelchair basketball athletes.